Impact of chirality on the aggregation modes of l-phenylalanine- and d-glucose-decorated phenylene–thiophene oligomers. (21st June 2021) - Hassan Omar, Omar; Falcone, Marta; Operamolla, Alessandra; Albano, Gianluigi
Abstract : Three l -phenylalanine- or d -glucose-decorated phenylene–thiophene oligomers have been studied using UV-Vis and ECD spectroscopies in different conditions of solution aggregation and thin films, investigating the impact of chirality on their aggregation modes. Abstract : The aggregation modes of three l -phenylalanine- or d -glucose-functionalized phenylene–thiophene oligomers were investigated using UV-Vis absorption and electronic circular dichroism (ECD) spectroscopies in different conditions of solution aggregation and thin films. The ECD measurements revealed superior capability to provide information about their first level of supramolecular organization and to detect the possible co-existence of multiple aggregation pathways, very difficult to identify by using only UV-Vis absorption. The impact on the (chiro)optical response of the nature of the chiral pendant group, especially in terms of intermolecular hydrogen bonding and steric hindrance, as well as that of the oligothiophene π-conjugated length, will be elucidated. The ability to recognize and control different aggregation modes could be very useful for the preparation of thin films of π-conjugated oligomers with highly tunable chiroptical features in view of optical sensing and other innovative opto-electronic applications.